A Full-Life-Cycle Public-Private Partnership Governance Model for Urban Parks in Japan: Experience and Inspiration - Jiarui LIU; Jia MA; Zelin SHANG; Xiong LI (Fengjing Yuanlin)
ObjectiveIntroducing social capital through the public-private partnership (PPP) model has become a crucial approach to enhancing the efficiency of park construction and operation. However, several pressing issues have emerged in practice that require urgent resolution. In November 2023, the State Council of China issued the Guiding Opinions on Standardizing the Implementation of a New Mechanism for Public-Private Partnerships, offering new opportunities to introduce social capital and innovative service models into park development. This research integrates theory and practice while drawing on Japan’s advanced experience in public-private cooperation for urban park governance. It explores new approaches to urban park construction and operation suited to China’s national conditions under the current policy context, providing insights and references for optimizing China’s PPP governance model in urban parks.MethodsFocusing on the PPP governance model for urban parks in Japan, this research examines official policies, project guidelines, implementation reports, and case studies issued by the Japanese government. Using literature review, comparative analysis, and historical research methods, the research first outlines the current state of urban park development in Japan and the challenges that have emerged during this process. It then introduces the background of Japan’s PPP models for urban parks and categorizes six fundamental approaches. By employing inductive reasoning and analyzing representative PPP cases, the research explores the development characteristics of Japan’s PPP model for urban parks. Furthermore, it identifies the advantages and limitations of the PPP model and, considering China’s national context, derives insights applicable to the construction and operation of urban parks in China.ResultsThe Japanese Ministry of Land, Infrastructure, Transport, and Tourism (MLIT) — the primary authority overseeing urban park development — has continually refined the PPP model under the framework of the PFI (private finance initiative) Act, and has gradually constructed a full-life-cycle PPP governance model that includes six major approaches: The Designated Administrator System, the PFI System, the Park-PFI System, the Urban Park Renovation Agreement System, the Installation-Management Permission System, and Public Facility Operation Projects. The full-life-cycle PPP governance model has formed a “space − time − assurance” three-in-one synergistic governance system. In the spatial dimension, it achieves a multi-layered, full-scale spatial coverage across the three levels of city, park and facility, facilitating the coordinated advancement of internal park governance and urban development. In the temporal dimension, it ensures a full-process closed-loop management system spanning multiple stages — construction, management, and operation — each supported by targeted and effective institutional designs to guarantee seamless transitions throughout the project lifecycle. In the assurance dimension, a comprehensive institutional support system is implemented, integrating legal regulations, dynamic supervision, and policy incentives. On this basis, the full-life-cycle PPP governance model establishes a stable and efficient collaborative framework, ensuring both the sustainability of projects and the fulfillment of public interest objectives. Through the PPP model, the Japanese government has successfully reduced financial and operational pressures while enhancing the quantity, scale, vibrancy, and quality of urban parks. Meanwhile, private enterprises involved in the PPP model have also gained substantial returns. Thanks to this, Japan’s urban park sector has embraced new opportunities for development, driven by a dynamic cycle of investment, vitality, and high quality.ConclusionThe PPP model for urban parks in Japan adopts a holistic full-life-cycle approach that vertically integrates the full-process stages of “construction − management − operation” through a “city − park − facility” multi-scale system. Complemented by a tridimensional safeguard mechanism encompassing “legal − regulatory − incentive” dimensions, the PPP model framework achieves comprehensive multidimensional coverage across the entire project lifecycle. It establishes an institutional closed-loop system that balances short-term implementation efficiency with long-term developmental resilience, ultimately realizing dual objectives of sustained urban spatial optimization and enduring enhancement of public welfare. Although Japan’s PPP practices face certain challenges, including issues of transparency, procedural complexity, limited capacities at the local government level, potential monopolization by large conglomerates, and a lack of diversified financing methods, the overall model still offers valuable insights for China. Given the similarities in political frameworks and developmental challenges between China and Japan, Japan’s experience suggests actionable inspirations for China, particularly with respect to refining the legal infrastructure, building a systematic and pragmatic implementation framework, ensuring adequate returns to attract private capital, and strengthening government regulation. Ultimately, such measures can strike a balance between encouraging social capital participation and safeguarding public interests, thereby facilitating the comprehensive transformation of urban parks from construction through long-term operation.